(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Most existing democratic countries have adopted the institution of the Ombudsman due to the objective need to protect human and civil rights and freedoms in the conditions of a modern state that extends legal regulation to all spheres of society, which strengthens the role and importance of the executive power and public administration in public life.